Menjawab Tantangan Pengasuhan Ibu Bekerja: Validasi Modul “Smart Parenting” untuk Meningkatkan Parental Self-Efficacy - Fitri Hayati; Arum Febriani (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
This study aimed to validate "Smart Parenting" a training module to increase the feeling of competence in carrying out the duties as a parent, or Parental Self-Efficacy (PSE) of working mothers with a toddler. The research was conducted using a quasi-experimental design in a model of untreated control group design with dependent pretest, posttest, and follow up among 12 participants. Six participants were in the treatment group, and the other six were in the control group. "Smart Parenting" was arranged based on Work-Family Balance and Domain-Specific Parenting for Toddler. The maternal self-efficacy was measured using the short version of Self-Efficacy for Parenting Tasks Index-Toddler Scale. The statistical analysis using Mann Whitney Test showed that there was a difference (p<0.05) in mother’s PSE between experimental group and control group. This research concluded that the "Smart Parenting" training program is effective for the purpose of increasing PSE for working mothers with toddlers.